The Second Semester Students’ Speaking Anxiety in English Language Education at Ganesha University of Education - Laksmi, I Gusti Ayu Rai; Ratminingsih, Ni Made; Dewi, Ni Luh Putu Eka Sulistia (The Art of Teaching English as a Foreign Language (TATEFL), 2021)
This study was aimed at identifying the type of anxiety and investigating the factors caused speaking anxiety in second semester students of English Language Education in UNDIKSHA. Mixed-method was used as the research design of this study in which random sampling technique was also used to determine the research sample. 70 second semester students were involved as the research sample. This research was done in online setting due to COVID-19 pandemic. The result of this study showed that there were two types of anxiety affected the second semester students, namely; state and trait anxiety. There were 26 % of second semester students influenced by state anxiety, 67% students were influenced by trait anxiety, and 7 % students were influenced by state and trait anxiety at the same time. In addition, it was also found that there were 5 internal and 11 external factors caused students’ speaking anxiety.